KEGIATAN CROSS CULTURE SEBAGAI STRATEGI PEMERINTAH KOTA SURABAYA DALAM MENINGKATKAN HUBUNGAN KERJASAMA SISTER CITY - Herning Suryo, Ayu Riandriani, Lusia Indrastuti & (Transformasi, 2015)
The purpose of this study is: To find out how the implementation of cross culture as local government strategy in running the cooperation of sister city relationships; and to examine the municipal government efforts to establish cooperative relations of sister cityMethods This was a qualitative descriptive study, the data used is qualitative data, that is data in the form of words, sentences, schematics and drawings. Location research in Surabaya City Government. While these types of data are: 1) Primary data, ie data obtained directly from interviews and direct observation to respondents in Surabaya city-government, 2) secondary data, ie data obtained from reference books or literature studies, documents, structure and other written sources.This study using multiple data collection techniques. Such techniques include: 1) observation, 2) Interview / Interview, and 3) Documentation. Research on cross culture activities in enhancing cooperation of sister city relationship indicates that keguatan cross culture is a form of soft diplomacy in improving the cooperation of sister city relationship. This is evidenced by the growing number of sister city cooperation list per year as well as an increase in various fields of cooperation with several countries that already woven.Keyword: sister city, relationships, government